Demographic history and population genetic analysis of Decapterus maruadsi from the northern South China Sea based on mitochondrial control region sequence - Su-Fang Niu; Ren-Xie Wu; Yun Zhai; Hao-Ran Zhang; Zhong-Lu Li; Zhen-Bang Liang; Yu-Hang Chen (PeerJ, 2019)
Late Pleistocene climate oscillations are believed to have greatly influenced the distribution, population dynamics, and genetic variation of many marine organisms in the western Pacific. However, the impact of the late Pleistocene climate cycles on the demographic history and population genetics of pelagic fish in the northern South China Sea (SCS) remains largely unexplored. In this study, we explored the demographic history, genetic structure, and genetic diversity of Decapterus maruadsi, a typical pelagic fish, over most of its range in the northern SCS. A 828–832 bp fragment of mitochondrial control region were sequenced in 241 individuals from 11 locations. High haplotype diversity (0.905–0.980) and low nucleotide diversity (0.00269–0.00849) was detected, revealing low levels of genetic diversity. Demographic history analysis revealed a pattern of decline and subsequent rapid growth in the effective population size during deglaciation, which showed that D. maruadsi experienced recent demographic expansion after a period of low effective population size. Genetic diversity, genetic structure, and phylogenetic relationship analysis all demonstrated that no significant genetic differentiation existed among the populations, indicating that D. maruadsi was panmictic throughout the northern SCS. Periodic sea-level changes, fluctuation of the East Asian Monsoon, and Kuroshio variability were responsible for the population decline and expansion of D. maruadsi. The demographic history was the primary reason for the low levels of genetic diversity and the lack of significant genetic structure. The life history characteristics and ocean currents also had a strong correlation with the genetic homogeneity of D. maruadsi. However, the genetic structure of the population (genetic homogeneity) is inconsistent with biological characteristics (significant difference), which is an important reminder to identify and manage the D. maruadsi population carefully.